Entre a geografia da ciência e a prática da ciência geográfica: uma narrativa sobre personagens de Montpellier, França - Dante F. C. Reis Junior (Confins)
In a recent experience, we went to the French city of Montpellier to get acquainted with the current panorama of researches dealing with “milieu-société” relations. As with earlier research, our initial purpose was to trace the intellectual trajectory of geographers who demonstrated a contemporary alignment with theoretical, systemic, and/or integrated approaches. Curiously, we come across the story of some characters who, not being all of them training geographers, practice research whose content is highly related to the thematic and methodological agendas of Geography. In addition, they share the vision of a science of social relevance. We started this article with elements of theoretical foundations and then summarized the professional biography of three interviewed characters. We conclude that their pathways and conceptions, while enclosing peculiarities, converge in certain aspects; for example, the defense of the “applied geography” tenet. The article is guided by the idea that scientific thought and practice have characteristics that can be explored from the point of view of the “geography” where both take place.